Colon metastasis from lung adenocarcinoma with BRAF V600E mutation: A case report - Luo, Yuhao; Mou, Kelin; Wang, Jianmei; Luo, Jing; Peng, Lin; Ye, Hua; Lin, Sheng (Frontiers in Immunology, 2022)
Symptomatic colon metastasis from primary lung cancer is rare in clinical practice. We report the case of a 58-year-old patient with advanced lung adenocarcinoma who developed abdominal symptoms, including abdominal distention and difficulty defecating, after immunotherapy and chemotherapy. The patient was diagnosed with lung adenocarcinoma, and systemic positron emission tomography-computed tomography confirmed multiple lymph node, pleural, and adrenal metastases. Molecular detection indicated BRAF V600E mutation and high programmed death-ligand 1 (PD-L1) expression. After first-line anti-programmed cell death protein 1 immunotherapy combined with chemotherapy, the nodes in the chest remarkably diminished. However, it was followed by colon obstruction, incomplete ileus, and bone metastasis. Endoscopic histological examination confirmed adenocarcinoma but could not identify primary or secondary tumors due to insufficient tissue. We performed colon resection to remove the obstruction, and postoperative tissue pathological microscopy confirmed metastasis from the lung adenocarcinoma. We corroborated the BRAF V600E mutation and high PD-L1 expression and supported the molecular features of lung adenocarcinoma. During hospitalization, the patient presented with unbearable pain in the bone metastases, and palliative radiotherapy was administered. Then, the patient received dabrafenib plus trametinib as the second-line therapy. This report discusses the clinical characteristics, pathology, imaging, molecular profile assessments, and treatment of primary lung adenocarcinoma with colon metastasis.